Behemoth's Penis, Yahweh's Might: Competing Bodies in the Book of Job. (March 2022) - Quick, Laura
The poetic description of Behemoth in Job 40 makes use of a literary technique for describing the body known as the was.f, elsewhere found most famously in biblical literature in the descriptions of the lovers in the Song of Songs (4.1-7; 5.11-16; 6.4-7; 7.2-10). In a was.f, body parts are systematically listed and described according to an organizing principle that develops its contents a capite ad calcem, beginning with the head and proceeding down the body. However, instead of providing a standard systematic itemization of this monstrous body, the book of Job subverts the was.f form. The description of Behemoth's body is truncated, making use of highly euphemistic language which focuses the reader upon one body part in particular: Behemoth's penis. Through the transformation of the was.f, the poet highlights and emphasizes the monster's massive genitalia. And because God is ultimately able to defeat the beast, the text therefore claims that Yahweh, so to speak, has the bigger balls. This paper explores the ideas and values embedded within the literary features and poetic devices employed in the description of Behemoth's body. In so doing, I uncover new implications for understanding the cosmic battle between Yahweh and the beast: as a divine willy-waving contest.